Pengaruh fasilitas wisata, kualitas pelayanan dan promosi terhadap kepuasan wisatawan di Kabupaten Pesisir Selatan - Wulandari, Arviana; Adi Cakranegara, Pandu; Widyo Widjajanti, Wiwik; Yaelt Lemus Vergara, Andrea (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of tourism facilities on tourist satisfaction in Pesisir Selatan Regency, to determine the effect of service quality on tourist satisfaction in Pesisir Selatan Regency, to determine the effect of promotion on tourist satisfaction in Pesisir Selatan Regency. The method used is quantitative research using descriptive, while data collection using a questionnaire. The sampling technique was non-probability sampling with purposive sampling as many as 115 respondents. The results of this study can be concluded that: (1) Tourist facilities have a positive and significant effect on tourist satisfaction in Pesisir Selatan Regency. (2) Service quality has a positive and significant effect on tourist satisfaction in Pesisir Selatan Regency. (3) Promotion has a positive and significant effect on tourist satisfaction in Pesisir Selatan Regency.